Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Advances in natural compounds modulating autophagy for the therapeutic intervention of heart failure - Jiaqian Tang; Chang Zhou; Mengyuan Li; Jing Tao; Ruying Deng; Xinyi Ouyang; Guomin Zhang; Huiping Liu (Molecular and Cellular Biochemistry, 2026)
Heart failure (HF) represents the terminal stage of multiple cardiovascular disorders and is characterized by substantial morbidity, disability, and mortality. Although standard pharmacotherapies offer partial symptomatic relief, their capacity to halt or reverse disease progression remains limited. In recent years, autophagy—an essential intracellular degradation and recycling process that safeguards cardiomyocyte homeostasis—has emerged as a critical determinant in the onset and progression of HF. In this review, we systematically examined approximately 170 research articles related to “natural compounds-autophagy-HF” published up to 2025, and synthesized major advances reported over the past five years. Based on chemical structure and natural source, representative bioactive compounds were categorized into five major classes: flavonoids, polyphenols, alkaloids, terpenoids, and marine-derived molecules. We then integrated evidence on the principal autophagy-regulatory signaling cascades influenced by these compounds, including the AMP-activated protein kinase (AMPK)/mechanistic target of rapamycin (mTOR) axis, phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt), sirtuin 1 (SIRT1)/forkhead box O (FOXO), BCL2/adenovirus E1B 19 kDa-interacting protein 3 (BNIP3)/NIP3-like protein X (NIX), and Beclin-1 pathways. Moreover, this review summarizes how these natural compounds modulate autophagy to attenuate key pathological processes associated with HF, including cardiac hypertrophy, adverse ventricular remodeling, mitochondrial dysfunction, and cardiomyocyte apoptosis. By comparing convergent mechanisms and compound-specific differences in autophagy-mediated cardioprotection, we highlight emerging mechanistic patterns and therapeutic implications. Collectively, through structured classification of compounds, integration of autophagy signaling pathways, and assessment of translational potential, this review provides a systematic framework to guide the rational application and further development of natural products for the prevention and treatment of HF. Graphical abstract

SFG enhances apoptosis of hepatocellular carcinoma by inhibiting tunneling nanotubes-mediated mitochondrial transport in the tumor microenvironment - Shasha Kong; Yuling Liu; Ruying Tang; Hui Li; Hongmei Lin; Longfei Lin (Apoptosis, 2026)

Effects of microplastics on N2O production and reduction potential in crop soils of northern China - Lei Zhong; Xinhao Li; Yuru Sun; Hui Xiao; Yafang Tang; Ruying Wang; Xiaoxuan Su (Chemosphere, 2024)

Phagocytosis of Microglia in the Central Nervous System Diseases - Ruying Fu; Qingyu Shen; Pengfei Xu; Jin Jun Luo; Yamei Tang (Molecular Neurobiology, 2014)